2000
DOI: 10.1038/sj.bmt.1702196
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and pharmacokinetics of cyclosporin A in relation to mode of infusion in bone marrow transplant patients

Abstract: Summary:Two main factors that affect the pharmacokinetics of cyclosporin A (CsA) during 24-h durable intravenous (DIV) administration have been reported, namely physiological changes after bone marrow transplantation, and blood sampling through indwelling lines. In addition, it has been found that infusion sets made of polyvinyl chloride (PVC) markedly adsorb CsA. We conducted in vitro adsorption studies of CsA on infusion sets, and the administration routes that are used in the treatment of patients with bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…1,2 To optimize the efficacy of CsA while minimizing the toxicity, therapeutic drug monitoring (TDM) is therefore essential. 1,2 To optimize the efficacy of CsA while minimizing the toxicity, therapeutic drug monitoring (TDM) is therefore essential.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…1,2 To optimize the efficacy of CsA while minimizing the toxicity, therapeutic drug monitoring (TDM) is therefore essential. 1,2 To optimize the efficacy of CsA while minimizing the toxicity, therapeutic drug monitoring (TDM) is therefore essential.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Immunosuppressive agents, such as cyclosporine, are defined by a narrow therapeutic window and low serum concentrations of these drugs might lead to acute graft rejection. Although a previous study suggested in vitro adsorption studies of cyclosporine on PVC infusion sets significantly higher than that in those made of polyethylene or polybutadiene [ 21 ], this study is the first to evaluate cyclosporine pharmacokinetics in ECMO patients. Our results suggested that cyclosporine concentration decreases slowly in the ECMO circuit with 66% of the initial concentration remaining in the circuit after 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of drug sorption into the administration set has been well documented. [ 1 3 ] Drug sorption can influence the prognosis of patients by preventing them from receiving the physician-intended drug dosage. Nitroglycerin is a nitrate used for vasodilation in patients with hypertension and ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%